Establishing the “Fit” between the Patient and the Therapy: The Role of Patient Gender in Selecting Psychological Therapy for Distressing Voices - Hayward, Mark; Slater, Luke; Berry, Katherine; Perona-Garcelán, Salvador (Frontiers in Psychology, 2016)
The experience of hearing distressing voices has recently attracted much attention in the literature on psychological therapies. A new ‘wave’ of therapies is considering voice hearing experiences within a relational framework. However, such therapies may have limited impact if they do not precisely target key psychological variables within the voice hearing experience and/or ensure there is a ‘fit’ between the profile of the hearer and the therapy (the so-called ‘What works for whom’ debate). Gender is one aspect of both the voice and the hearer (and the interaction between the two) that may be influential when selecting an appropriate therapy, and is an issue that has thus far received little attention within the literature. The existing literature suggests that some differences in voice hearing experience are evident between the genders. Furthermore, studies exploring interpersonal relating in men and women more generally suggest differences within intimate relationships in terms of distancing and emotionality. The current study utilised data from four published studies to explore the extent to which these gender differences in social relating may extend to relating within the voice hearing experience. The findings suggest a role for gender as a variable that can be considered when identifying an appropriate psychological therapy for a given hearer.